Strategi Peningkatan Kinerja Dosen Pendidikan Ekonomi Unpam Di Masa Pandemi Covid-19 - Syafaatul Hidayati; Syamsul Anwar; Badrus Sholeh (Universitas Hamzanwadi, 2022)
The purpose of this research is to find out the strategy for developing lecturers' performance during the COVID-19 pandemic